2020
DOI: 10.3390/ph13120427
|View full text |Cite
|
Sign up to set email alerts
|

Where Does Metformin Stand in Modern Day Management of Type 2 Diabetes?

Abstract: Metformin is the most commonly used glucose-lowering therapy (GLT) worldwide and remains the first-line therapy for newly diagnosed individuals with type 2 diabetes (T2D) in management algorithms and guidelines after the UK Prospective Diabetes Study (UKPDS) showed cardiovascular mortality benefits in the overweight population using metformin. However, the improved Major Adverse Cardiovascular Events (MACE) realised in some of the recent large cardiovascular outcomes trials (CVOTs) using sodium-glucose co-tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 143 publications
(171 reference statements)
0
27
0
Order By: Relevance
“…While the use of sulphonylureas could possibly be further explored for the improvement in ESRD, this must be weighed upon their hypoglycaemic risk. Furthermore, this study could not determine the effects of metformin on renal outcomes 51,70 71,72 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…While the use of sulphonylureas could possibly be further explored for the improvement in ESRD, this must be weighed upon their hypoglycaemic risk. Furthermore, this study could not determine the effects of metformin on renal outcomes 51,70 71,72 .…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, this study could not determine the effects of metformin on renal outcomes. 51,70 Nevertheless, additional data from ongoing trials (RenoMet, VA-IMPACT) will hopefully further elucidate the cardiovascular and renal protective effect of metformin. 71,72 As such, further work is required to define the cardiorenal profile of these drugs to better inform clinical practice.…”
Section: Benefitmentioning
confidence: 99%
“…In addition: "Metformin prescribing peaked from 55.4% in 2000 to 83.6% in 2013 among all individuals with T2D who were on at least Ahmad et al 2020, [20] Sharma et al, [21] Montvida et al [22] (continued on next page) C.R. Triggle et al skeletal muscle insulin sensitivity (90% versus 55%) [41].…”
Section: Risk-benefits Of Chronic Metformin Usementioning
confidence: 99%
“…Experimental data have demonstrated that metformin reduces inflammation, exerts beneficial effects on lipids, exhibits antithrombotic and anti-atherosclerotic activity, and improves both the gut microbiome and endothelial cell function. 20 In patients with T2D and coronary artery disease, there is evidence to support that metformin exerts a cardioprotective effect by altering cardiac metabolism, which in turn improves cardiac function. 21 …”
Section: Methodsmentioning
confidence: 99%